2014
DOI: 10.1172/jci68901
|View full text |Cite
|
Sign up to set email alerts
|

NOTCH inhibits osteoblast formation in inflammatory arthritis via noncanonical NF-κB

Abstract: NOTCH-dependent signaling pathways are critical for normal bone remodeling; however, it is unclear if dysfunctional NOTCH activation contributes to inflammation-mediated bone loss, as observed in rheumatoid arthritis (RA) patients. We performed RNA sequencing and pathway analyses in mesenchymal stem cells (MSCs) isolated from transgenic TNF-expressing mice, a model of RA, to identify pathways responsible for decreased osteoblast differentiation. 53 pathways were dysregulated in MSCs from RA mice, among which e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 63 publications
1
80
0
Order By: Relevance
“…Inhibition of Notch signalling promotes osteoblast activity, while activation of Notch signalling inhibits osteoblast function in vitro . 41 Moreover, targeted inactivation of Hes1 in osteoblasts increased the trabecular bone volume and the trabecular number,42 while inhibition of Notch signalling ameliorated tumour necrosis factor alpha-induced bone loss and stimulated osteoblast activity in mice 43. As described previously, subchondral bone formation was also accompanied by locally enhanced osteoclastogenesis 44.…”
Section: Discussionmentioning
confidence: 71%
“…Inhibition of Notch signalling promotes osteoblast activity, while activation of Notch signalling inhibits osteoblast function in vitro . 41 Moreover, targeted inactivation of Hes1 in osteoblasts increased the trabecular bone volume and the trabecular number,42 while inhibition of Notch signalling ameliorated tumour necrosis factor alpha-induced bone loss and stimulated osteoblast activity in mice 43. As described previously, subchondral bone formation was also accompanied by locally enhanced osteoclastogenesis 44.…”
Section: Discussionmentioning
confidence: 71%
“…Interestingly, a recent study on osteoarthritis (OA) showed that an intra-articular injection of DAPT significantly suppresses joint-destruction in (Col2a1)-Cre ERT / Rbpj fl/fl OA mice (Hosaka et al, 2013). In addition, DAPT treatment of mice overexpressing TNFα that causes inflammatory bone resorption also effectively suppresses systemic osteoporotic phenotype (Zhang et al, 2014). Since DAPT efficiently inhibited the observed bone absorption in the osteoclast-specific Fbw7 conditional knockout mice, Notch signaling could be a potential target for treating various bone absorptic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study may provide some understanding of how transient Notch inhibition enhances chondrogenic and osteogenic differentiation from MSCs in the inflammatory setting of fracture repair. Zhang et al [38] demonstrated that chronic inflammation increased the expression of non-canonical NF-κB proteins, which activated Notch signaling by binding to and promoting nuclear translocation of NICD. Additionally, this inflammation mediated Notch activation in MSCs suppressed osteogenic differentiation, which could be prevented by administration of the Notch inhibitor, DAPT.…”
Section: Discussionmentioning
confidence: 99%